The influence of healthy lifestyle and price perception on purchase Warung Ahin Vegetarian Medan - Sinaga, Hommy Dorthy Ellyany; Manik, Desma Erica Maryati; Waty, Venny (Privietlab, 2025)
This study investigates the influence of a healthy lifestyle and price perception on purchase intention at Ahin Vegetarian in Medan. Employing a quantitative research design with primary data sources, the research targets prospective consumers who intend to make purchases at Ahin Vegetarian during the 2024 period, although the exact population size remains unknown. A total of 110 respondents were selected using incidental sampling techniques. The results of the partial t-test indicate that a healthy lifestyle does not have a statistically significant effect on purchase intention. Conversely, price perception shows a significant and positive impact on consumers’ intention to buy. The findings from the simultaneous test demonstrate that both variables, healthy lifestyle and price perception, jointly exert a significant influence on purchase intention. Furthermore, the coefficient of determination (R²) reveals that a portion of the variation in purchase intention can be explained by these two independent variables. These results suggest that while health-oriented behaviors may shape general consumer attitudes, price perception is a more decisive factor in influencing specific purchasing decisions within the vegetarian food market. This study provides practical implications for business owners and marketers in the vegetarian food industry, highlighting the importance of perceived price value in stimulating consumer interest and enhancing sales performance.